KEY FEATURES OF HUMAN NUTRITION BEHAVIOR - Rabadanova,; Bogatyreva,; Artemyeva,; Aralova,; Polozhentseva,; Pisarevsky, (Revista Inclusiones, 2019)
The importance of nutrition for the human organism cannot be overestimated. It provides all organs with plastic and energetic material and supports viability. Unfortunately, in the developed world nutrition is not always balanced and safe. It is known that in recent years, the average body weight of a person has increased significantly. It provides a framework for establishing the importance of the detailed study of nutrition behavior and the role that the brain plays in it. It has been found that the role of the brain in nutrition behavior is very multifaceted; at the same time the bark and the subcortex both obviously play an important role in this process.